The Effectiveness of a Nurse-led Cervical Cancer Prevention Program Among Reproductive-age Women in Selected Areas of Chennai - V. Yamunarani; B. Lingeswari (International Journal of Oncological Nursing and Practices, 2024)
Background: Cervical cancer remains a major global health issue, significantly impacting women's health. Early detection and preventive measures through screening, along with enhanced awareness, are vital in lowering mortality rates associated with this disease. This study aimed to evaluate the effectiveness of a nurse-led cervical cancer prevention program in improving knowledge and practice related to cervical cancer prevention among women. Methods: This quasi-experimental study was conducted with 60 women divided into an experimental group and a control group, each consisting of 30 participants. The experimental group received a nurse-led cervical cancer prevention program, while the control group received no intervention. Data were collected using pretest and post-test assessments on knowledge and practice levels regarding cervical cancer prevention. Statistical analyses utilized Student’s independent t-tests and paired t-tests to evaluate the significance of changes in knowledge and practice scores. Results: It indicated that the socio-demographic characteristics of both groups were comparable regarding age, education level, occupation, family income, and marital status. Pretest results showed that both groups had inadequate knowledge and poor practice levels concerning cervical cancer prevention. Post-intervention, the experimental group demonstrated a significant improvement in both knowledge and practice levels, with all participants moving from inadequate to moderate or adequate knowledge levels and none showing poor practice. In contrast, the control group still exhibited high levels of inadequate knowledge and poor practice. Statistical analyses confirmed that the improvements in the experimental group were highly significant (p<0.001). Conclusion: The study highlights the effectiveness of the nurse-led cervical cancer prevention program in significantly enhancing both knowledge and practice regarding cervical cancer among women in the experimental group. This intervention led to a marked improvement in cervical cancer awareness and preventive practices, underscoring the importance of educational programs in combating cervical cancer.
Keywords: cervical cancer; knowledge improvement; nurse-led intervention; practice improvement; prevention program; screening; women's health